+0

# How to Solve for x

0
123
2

log4 6 + log4 (x + 1) = 2

Guest Apr 4, 2017

#2
+79823
+2

log4 6 + log4 (x + 1) = 2

We can write

log4 [6 * (x + 1) ]  = 2

In exponential form, we have

4^2   =  6 (x + 1)    simplify

16 = 6x + 6      subtract 6 from both sides

10  = 6x      divide both sides by 6

10/ 6  = x  =   5/3

CPhill  Apr 4, 2017
Sort:

#1
+1

Solve for x:
(log(6))/(log(4)) + (log(x + 1))/(log(4)) = 2

Rewrite the left hand side by combining fractions. (log(6))/(log(4)) + (log(x + 1))/(log(4)) = (log(6) + log(x + 1))/(log(4)):
(log(6) + log(x + 1))/(log(4)) = 2

Multiply both sides by log(4):
log(6) + log(x + 1) = 2 log(4)

Subtract log(6) from both sides:
log(x + 1) = 2 log(4) - log(6)

2 log(4) - log(6) = log(4^2) + log(1/6) = log(16) + log(1/6) = log(16/6) = log(8/3):
log(x + 1) = log(8/3)

Cancel logarithms by taking exp of both sides:
x + 1 = 8/3

Subtract 1 from both sides:

Guest Apr 4, 2017
#2
+79823
+2

log4 6 + log4 (x + 1) = 2

We can write

log4 [6 * (x + 1) ]  = 2

In exponential form, we have

4^2   =  6 (x + 1)    simplify

16 = 6x + 6      subtract 6 from both sides

10  = 6x      divide both sides by 6

10/ 6  = x  =   5/3

CPhill  Apr 4, 2017

### 26 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details